Re-imagining Professional Experience in Initial Teacher Education Narratives of Learning (Springer Singapore, 2018)
This book takes a fresh look at 'professional experience' in initial teacher education in Australia. Using collaborative narrative methodologies, the authors critically explore the ways in which one faculty of education engages with schools, industry, the teaching profession and government policy to deliver an innovative professional experience program. It includes chapters offering new perspectives on more traditional practicums in schools, as well as those reporting on exciting partnership initiatives where pre-service teachers, teacher educators and practitioners work together to teach and learn in new and mutually beneficial ways. There is a particular focus on the professional learning of all stakeholders from across the professional experience program. The book allows readers to gain a new understanding of the experiences and learning opportunities available to all stakeholders when a professional experience program makes a priority of boundary work, relational work and identity work. With the critical and creative power of narrative to convey what other research methodologies cannot, it shows how one institution has developed a variety of innovative approaches and structures in response to on-going debates on quality in teacher education, the role of educational partnerships in teacher preparation and the personal and professional insights gained from such opportunities.